A New Variety of Delphinium malabaricum (Huth) Munz from the Western Ghats - Billore, K. V. (Indian Forester, 1973)
An interesting new variety of Delphintum Linn. i.e. D. malabaricum var. ghaticum var. nov. is described and illustrated.